The effect of nursing ethics education through narration and lecture methods on patient advocacy by nurses in Iran in 2017: A quasi-experimental study - Nasrin Imanifar; Milad Derikvand; Seyyed Abolfazl Vagharseyyedin (Journal of Multidisciplinary Care, 2022)
Background and aims: Patient advocacy role in nursing is affected by several barriers, such as the lack of nurses’ ethical knowledge about their roles as patient advocators. Since this role can be learned, these barriers may be overcome by education through an effective method. The present study aimed to investigate the effect of ethics education on nurses’ patient advocacy using ethics narration and lecture compared to a control group. Methods: This quasi-experimental, three-group design study was conducted among nurses of hospitals in Birjand, South Khorasan province in 2016-2017. The sample size (n) was 27 in the narration group, 26 in the lecture group, and 22 in the control group. We used the Protective Nursing Advocacy Scale (PNAS) developed by Hanks to collect data, whose validity and reliability have been confirmed in Iran. Data analysis was performed using a trial version of SPSS 22 by descriptive and analytical statistics appropriate to the research objectives. Results: The results of comparing the three groups after eliminating the effect of age indicated that lecture-based education increased the total patient advocacy (P<0.05) and the impact of education and environment (P<0.05) significantly compared with the control group. However, the narration method did not show any significant difference to the control group. Conclusion: The lecture and narration methods increased nurses’ patient advocacy. We recommend combining the two methods to achieve better outcomes.